Antara Hak dan Utang : Kajian Hukum terhadap Dampak Kepailitan Sritex terhadap Buruh dan Pemilik - Ety Isworo; Wiwik Yulianti; Femmy Silaswaty Faried (Pemuliaan Keadilan, 2025)
The bankruptcy of a major company like PT Sri Rejeki Isman Tbk (Sritex) not only reflects a financial crisis but also opens a significant debate about legal fairness for stakeholders, particularly laborers and company owners. This research examines the impact of the bankruptcy on the fulfillment of laborers' normative rights and the legal protection afforded to company owners. Using a juridical-normative approach and a case study method, the findings reveal that the bankruptcy process still presents imbalances in legal protection, especially for laborers who, despite being legally recognized as preferential creditors, are often disregarded in practice. This article recommends regulatory reform and strengthening the state's role in ensuring justice throughout the bankruptcy proceedings.